Treatment of respiratory infections in pregnant patients: overview - KOCAKAYA, DERYA (Springer Nature, 2022)
It is reported that antibiotics represent almost 80% of the drugs prescribed to pregnant women and that between 1 in 5 and 1 in 4 pregnant women are administered antibiotic pharmacotherapy [1–3]. In pregnant women, the most frequently occurring infections are urinary tract infections (UTIs) (cystitis and pyelonephritis), venereal infections and the upper respiratory tract infections (URTIs)